2017
DOI: 10.1016/j.bbalip.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-senescent keratinocytes organize in plasma membrane submicrometric lipid domains enriched in sphingomyelin and involved in re-epithelialization

Abstract: Membrane lipid raft model has long been debated, but recently the concept of lipid submicrometric domains has emerged to characterize larger (micrometric) and more stable lipid membrane domains. Such domains organize signaling platforms involved in normal or pathological conditions. In this study, adhering human keratinocytes were investigated for their ability to organize such specialized lipid domains. Successful fluorescent probing of lipid domains, by either inserting exogenous sphingomyelin (BODIPY-SM) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…super resolution microscopy or fluorescence lifetime spectroscopy) [13][14][15][16] and more relevant lipid probes [17,18] have allowed to evidence bigger (submicrometric instead of nanometric) and more stable lipid domains. Those have been observed on prokaryotic cells [19], yeast [20,21] and various eukaryotic cells like keratinocytes [22], fibroblasts [23] and RBCs [24][25][26]. Focus is generally made on sphingolipids and sterols as they are two major lipids of the PM external leaflet of many cells and because they are known to be enriched in rafts and associated with membrane fluidity regulation.…”
Section: Introductionmentioning
confidence: 99%
“…super resolution microscopy or fluorescence lifetime spectroscopy) [13][14][15][16] and more relevant lipid probes [17,18] have allowed to evidence bigger (submicrometric instead of nanometric) and more stable lipid domains. Those have been observed on prokaryotic cells [19], yeast [20,21] and various eukaryotic cells like keratinocytes [22], fibroblasts [23] and RBCs [24][25][26]. Focus is generally made on sphingolipids and sterols as they are two major lipids of the PM external leaflet of many cells and because they are known to be enriched in rafts and associated with membrane fluidity regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The signal obtained was predominantly concentrated around the plasma membrane [65]. The heterogeneity of lysenin staining was also described and the overall signal declined as the cells reached senescence [65].…”
Section: C6-nbd Sphingomyelin (Abbreviated Fsm In This Thesis) Manufmentioning
confidence: 84%
“…Colocalization of lysenin with FSM signal was quantified, and Mound demonstrated that lysenin signal diminished after the addition of SMase, an enzyme that degrades SM [65]. The signal obtained was predominantly concentrated around the plasma membrane [65]. The heterogeneity of lysenin staining was also described and the overall signal declined as the cells reached senescence [65].…”
Section: C6-nbd Sphingomyelin (Abbreviated Fsm In This Thesis) Manufmentioning
confidence: 99%
See 2 more Smart Citations